The Effect of the FIFA 11+ in increasing Cardiovascular Fitness in Cirebon Distiric Football Referees - Risa Hadi; Harun Harun; Supriadi Supriadi (Plyometric : Jurnal Sains dan Pendidikan Keolahragaan, 2022)
Cardiovascular endurance is severely taxed, the referees must be alert and fatigue will not impair their decision-making. FIFA 11+ have potention not only for injury prevention buat also for increasing fitness for referees. The aim of this study is to examine the effects of FIFA 11+ program on cardiovascular endurance among male Cirebon District Football referees Experimental one group pretest-posttest design in 15 male football referee 33,7±3,5 years old, FIFA 11+ program done in 4 weeks, 3 times per week. Multistage running test is used as parameter cardiovascular endurance. Collected data is analysed by descriptive statistictic and t-test. Te result showed that cardiovascular endurance increases 4,30 ml/kg/min, that t score= 16,665>1,761. This show that FIFA 11+ significant increasing cardiovascular endurance. The Fifa 11+ show that significant increasing cardiovascular endurance in male football referees Cirebon District.